2015
DOI: 10.1103/physreve.92.063102
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale behavior of Hall magnetohydrodynamic turbulence

Abstract: Decaying Hall magnetohydrodynamic (HMHD) turbulence is studied using three-dimensional (3D) direct numerical simulations with grids up to 768 3 points and two different types of initial conditions. Results are compared to analogous magnetohydrodynamic (MHD) runs and both Laplacian and Laplacian squared dissipative operators are examined. At scales below the ion inertial length, the ratio of magnetic to kinetic energy as a function of wave number transitions to a magnetically dominated state. The transition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
2
14
0
Order By: Relevance
“…As f approaches f c i , U e ,⊥ and U i ,⊥ diverge with U e ,⊥ becoming shallower similar to E ⊥ , which is consistent with ions decoupling at these frequencies while the electrons remain frozen to the field. U i ,⊥ also becomes steeper than B ⊥ in this range consistent with simulations [e.g., Franci et al , ; Stawarz and Pouquet , ]. The divergence of U i ,⊥ and U e ,⊥ spectra begins at k ⊥ ρ i <1 and may be consistent with the ion inertial length, which is located at k ⊥ ρ i ≈0.65.…”
Section: Discussionsupporting
confidence: 85%
“…As f approaches f c i , U e ,⊥ and U i ,⊥ diverge with U e ,⊥ becoming shallower similar to E ⊥ , which is consistent with ions decoupling at these frequencies while the electrons remain frozen to the field. U i ,⊥ also becomes steeper than B ⊥ in this range consistent with simulations [e.g., Franci et al , ; Stawarz and Pouquet , ]. The divergence of U i ,⊥ and U e ,⊥ spectra begins at k ⊥ ρ i <1 and may be consistent with the ion inertial length, which is located at k ⊥ ρ i ≈0.65.…”
Section: Discussionsupporting
confidence: 85%
“…The magnetic field is expressed in Alfvén velocity units, P is the pressure, and J = ∇ × B the current density; ν and η are the kinematic viscosity and magnetic diffusivity, and ν ′ and η ′ are hyperviscosity and hyperdiffusivity coefficients associated with bi‐Laplacian terms. Their respective roles on the formation of small‐scale current sheets are discussed in detail in Stawarz & Pouquet (; see also Figure , for which we took ν = η , ν ′ = 0 = η ′ . )…”
Section: Coupling To a Magnetic Fieldmentioning
confidence: 99%
“…Thus, the dynamical interactions between small and helicity spectra are constrained by a relation stemming from their conservation, providing a lack of uniqueness in power-law steady-state solutions (see [62] for the case of the cross-correlation between the velocity and magnetic field in MHD). Finally, in [63], it was shown that, for the small-scale behavior of Hall MHD in the decaying case, magnetic energy becomes dominant at sub-ionic scales, with narrow and intense current structures in which one observes a strong alignment between the current and the magnetic field (leading to force-free fields), as well as a narrow electric field auto-correlation function. On the other hand, the large-scale behavior of Hall-MHD, close to the ion inertial scale, has been much less investigated.…”
Section: Introductionmentioning
confidence: 99%